Vagus Nerve and Stomach Synucleinopathy in Parkinson’s Disease, Incidental Lewy Body Disease, and Normal Elderly Subjects: Evidence Against the “Body-First” Hypothesis - Beach, Thomas G.; Adler, Charles H.; Sue, Lucia I.; Shill, Holly A.; Driver-Dunckley, Erika; Mehta, Shyamal H.; Intorcia, Anthony J.; Glass, Michael J.; Walker, Jessica E.; Arce, Richard; Nelson, Courtney M.; Serrano, Geidy E. (Journal of Parkinson's disease, 2021)
Background: Braak and others have proposed that Lewy-type α-synucleinopathy in Parkinson’s disease (PD) may arise from an exogenous pathogen that passes across the gastric mucosa and then is retrogradely transported up the vagus nerve to the medulla. Objective: We tested this hypothesis by immunohistochemically staining, with a method specific for p-serine 129 α-synuclein (pSyn), stomach and vagus nerve tissue from an autopsy series of 111 normal elderly subjects, 33 with incidental Lewy body disease (ILBD) and 53 with PD. Methods: Vagus nerve samples were taken adjacent to the carotid artery in the neck. Stomach samples were taken from the gastric body, midway along the greater curvature. Formalin-fixed paraffin-embedded sections were immunohistochemically stained for pSyn, shown to be highly specific and sensitive for α-synuclein pathology. Results: Median disease duration for the PD group was 13 years. In the vagus nerve none of the 111 normal subjects had pSyn in the vagus, while 12/26 ILBD (46%) and 32/36 PD (89%) subjects were pSyn-positive. In the stomach none of the 102 normal subjects had pSyn while 5/30 (17%) ILBD and 42/52 (81%) of PD subjects were pSyn-positive. Conclusion: As there was no pSyn in the vagus nerve or stomach of subjects without brain pSyn, these results support initiation of pSyn in the brain. The presence of pSyn in the vagus nerve and stomach of a subset of ILBD cases indicates that synucleinopathy within the peripheral nervous system may occur, within a subset of individuals, at preclinical stages of Lewy body disease.